Misconceptions on Multiplication Material in Grade IV Elementary School Based on Newman's Procedure - Istiqomah,; Herman, Tatang; Salma Dwihandha Putri, Febrialita; Rania Kirana, Cut (International Conference on Elementary Education, 2025)
This study aims to describe the misconceptions of fourth grade elementary school students in solving multiplication problems through error analysis based on the Newman procedure. The approach used is descriptive qualitative, with 13 students selected by purposive sampling as research subjects. Data were obtained through tests and in-depth interviews to understand the patterns of students' errors at each stage of solving multiplication problems. The Newman procedure was used as an analysis framework, which includes five stages: understanding the problem, translating the problem, performing operations, writing answers, and rechecking the answers. The results showed that students experienced misconceptions at various stages of problem solving, especially at the stages of understanding the problem and translating the problem. Students tended to misinterpret multiplication operations and made mistakes in calculating nested multiplication. These findings indicate that misconceptions at the early stages can have an impact on subsequent errors that hinder the success of solving the problem as a whole. Based on the results of the study, it is hoped that teachers can develop more effective learning strategies to help students understand the concept of multiplication in depth and prevent misconceptions from occurring.